Quantitative Portal Vein Velocity of Liver Cancer Patients with Transcatheter Arterial Chemoembolization on Angiography - Yung-Jen Ho; Mu-Bai Chang; Yang-Hsien Lin; Chun-Hsu Yao; Tzung-Chi Huang (The Scientific World Journal)
Objective. We applied optical flow method (OFM) to quantify relative velocities of blood flow using digital subtraction angiography (DSA) in the vascular analysis of hepatocellular carcinoma (HCC) patients who underwent transarterial chemoembolization (TACE) treatment. Methods. A total of 40 HCC patients treated by TACE were analyzed in this study. DSA imaging with a 12-inch field of view, 1024 × 1024 pixels and 4 frames/second was acquired. OFM developed for motion estimation is applied for blood flow estimation. Two acrylic phantoms were built to validate the method. Results. The relationship between the OFM and Doppler measurements was found linear with R2=0.99 for both straight and curved tube phantoms. Quantitative blood flow distribution images of the portal vein region were presented. After TACE, the minimum, maximum and mean velocities in the portal vein all decreased (P<0.05). Additionally, the velocity in the portal vein is significantly lower with a higher Child-Pugh score (P<0.01). Conclusions. The present technique provides add-on quantitative information of flows to DSA and the hemodynamic analysis in relative quantifications of blood flow in portal vein of hepatocellular carcinoma patients using DSA.